Correlation between EPB Entrapment Test and Ultrasound Wrist Findings in Patients with De Quervain's Disease - Vijayaraja Elangovan; Srinivasan Rajappa; Gokul K Jeganathan; Lokesh K Sekaran (Journal of Orthopedics and Joint Surgery)
Introduction: The reliability of clinical tests in diagnosing de Quervain's disease has been established, but the presence of subcompartmentalization is difficult to identify, which gave the origin of the extensor pollicis brevis (EPB) entrapment test. Diagnosis of several other anatomical variations like a bony crest, multiple abductor pollicis longus (APL), and EPB slips are necessary. However, surgical inspection is the gold standard method for diagnosing anatomical variation, but the improvement in diagnostic efficacy for better prognosis by combining clinical and ultrasound examination is to be assessed. Aim: To determine the correlation between EPB entrapment test and ultrasound wrist findings in patients with de Quervain's tenosynovitis in the detection of anatomical variations of the first extensor compartment. Materials and methods: A total of 40 Finkelstein's test-positive wrists underwent EPB entrapment test and ultrasonography (USG) examination by a surgeon and a radiologist, respectively. Radiological evidence of sub-compartmentalization and other anatomical variations were recorded. Both the surgeon and radiologist were blinded to each other's results. Surgery was done as a reference standard. Results: The sensitivity of the EPB entrapment test in identifying the sub-compartmentalization is 73.6%, and that of the ultrasound examination is 97.4%, with a majority of the distal incomplete septum (75%). The mean number of APL slips was three, and one wrist had multiple EPB slips.3 Ultrasound also showed a bony crest in the radial styloid of 39 wrists (97.5%) Conclusion: The extensor pollicis brevis (EPB) entrapment test, a reliable and simple clinical test for identifying sub-compartmentalization of the first extensor compartment but in combination with ultrasound examination, which identifies anatomical variations, could be vital in deciding appropriate treatment and effective surgical release, thereby preventing treatment failures.